Cytologic analysis of pancreatic juice increases specificity of detection of malignant IPMN-A systematic review - Tanaka, Masayuki; Heckler, Max; Liu, Bing; Heger, Ulrike; Hackert, Thilo; Michalski, Christoph (Clinical gastroenterology and hepatology, 2019)
Biomarker, diagnostic, neoplasm, pancreatic cyst
Gesehen am 14.10.2019